2019
DOI: 10.1016/j.commatsci.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary induced deformation mechanisms in nanocrystalline Al by molecular dynamics simulation: From interatomic potential perspective

Abstract: Nanocrystalline metals exhibit many excellent mechanical properties and their underlying deformation mechanisms have been studying widespread. The well-designed atomistic simulations can predict the mechanical behavior of materials ahead of experiments and provide sufficient information on the atomic scale. The choice of appropriate interatomic potential is one of the main concerns of any atomistic simulation that needs to be seriously considered in order to obtain reliable results. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…Note that grain boundary-mediated scenarios included in Yamakov’s deformation model 34 have also been suggested for the plasticity of other material systems such as the deformation mechanism of the Al-Cu joint under tensile loading 35 and grain size dependence of tensile behavior in nanocrystalline Ni-Fe 36 . Also, atomistic simulations are able to shed further light on grain boundary-induced deformation (see eg 37,38 ). On the other hand, the multilayer system with a layer thickness of 100 nm resulted in different behavior which means that dislocation-mediated deformation should be in charge for the observed higher friction behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Note that grain boundary-mediated scenarios included in Yamakov’s deformation model 34 have also been suggested for the plasticity of other material systems such as the deformation mechanism of the Al-Cu joint under tensile loading 35 and grain size dependence of tensile behavior in nanocrystalline Ni-Fe 36 . Also, atomistic simulations are able to shed further light on grain boundary-induced deformation (see eg 37,38 ). On the other hand, the multilayer system with a layer thickness of 100 nm resulted in different behavior which means that dislocation-mediated deformation should be in charge for the observed higher friction behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This deviation is mainly attributed to the grain boundaries in the polycrystal sample. Experiments and simulations have proved that the existence of grain boundaries has an important effect on the mechanical properties of materials [41][42][43][44]. As mentioned, the yield stress depends mainly on the nucleation of the first set of dislocations [24].…”
Section: Prediction On Hea Polycrystalmentioning
confidence: 99%
“…On the other hand, Young's modulus is sensitive to the chemical composition and the intrinsic structure of materials. Simulations have shown that Young's modulus decreases with the increase of the grain boundary volume fraction [43], especially when the grain size drops to the nanocrystalline region (<100 nm) [44]. While the single-crystal sample has a single fcc structure (green atoms), and for the polycrystal samples, the atoms at grain boundary regions contribute a new disordered structure (blue atoms).…”
Section: Prediction On Hea Polycrystalmentioning
confidence: 99%
“…In this study, we used atomistic simulations to explore the underlying atomic-level mechanisms of GB segregation strengthening of NC Al by doping Mg atoms. Fully three dimensional (3D) polycrystalline models for both pure Al and Al-5%Mg were used to avoid the geometric limitations of 2D or 3D columnar polycrystalline models [20]. A hybrid MC/MD method was used to obtain the equilibrium distribution of Mg atoms in the Al-Mg alloy model.…”
Section: Introductionmentioning
confidence: 99%